Robotic-Assisted Isolated Polyethylene Exchange: A Novel Surgical Technique - Liam Cleary, MD; Alec McCann, MD; Jake Peterson, MS; Caleb Pawl, MD; Matthew Brown, MD; Alex Caughran, MD; David Markel, MD; Matthew Bullock, DO, MPT (Arthroplasty Today)
An isolated polyethylene exchange (IPE) is a revision procedure with mixed results in the literature, typically indicated for well-aligned total knee arthroplasties with instability. Surgeons often rely on subjective feedback and experience to determine whether an IPE or a more involved revision procedure is necessary. The technique of robotic-assisted IPE offers the potential for more precise decision-making in revision knee arthroplasty. Robotic systems can provide intraoperative data that may help identify ideal candidates for IPE and guide the selection of the appropriate PE component to address instability. Future studies comparing robotic-assisted IPE with traditional methods are needed to investigate patient-reported outcomes and functional results.